USING ARTIFICIAL INTELLIGENCE TO IMPROVE SPEECH COMPETENCE - Zulfizar Rustamovna Karimova (Journals Park Publishing, 2025)
This paper explores the role of artificial intelligence (AI) in enhancing speech competence. With the increasing global demand for effective communication skills, AI-driven technologies such as speech recognition, natural language processing, and machine learning provide innovative approaches to improving speech proficiency. This study examines AI-based applications, including virtual tutors, speech assessment tools, and interactive conversation agents, to analyze their effectiveness in speech training. Additionally, the paper discusses the advantages and challenges of implementing AI in speech education and highlights future prospects for AI-powered communication training.
Keywords: Artificial intelligence, speech competence, speech training, machine learning, natural language processing, virtual tutors.